Adding fish oil to whey protein, carbohydrate and vitamin D improves eccentric-exercise recovery in soccer players - Philpott, J. D.; Donnelly, C.; Walshe, I. H.; Hick, J.; Galloway, S.; Tipton, K. D.; Witard, O. C. (International Journal of Sport Nutrition and Exercise Metabolism, 2017)
xSoccer players often experience eccentric exercise-induced muscle damage due to the physical demands of soccer matchplay. An improved muscle functional recovery from eccentric exercise has been shown with protein feeding. Since fish oil derived n-3 polyunsaturated fatty acids (n-3PUFA) exhibit anti-inflammatory properties, combining fish oil with protein may facilitate recovery. Therefore, the primary aim of the present study was to assess the influence of 6 wk supplementation with a multi-ingredient beverage containing a combination of n-3PUFA, whey protein and vitamin D on muscle function and soreness, inflammation and soccer performance during exercise recovery. Competitive soccer players (n=30) were assigned to one of three conditions. The experimental condition (FO) contained n-3PUFA (550 mg DHA, 550 mg EPA), whey protein (15 g) and vitamin D (3 µg). The protein control (PRO) contained whey protein (15 g) and vitamin D (3.9 µg) and the eucaloric control condition (CHO) contained carbohydrate. Eccentric exercise consisted of 12 sets of unilateral knee extension/flexion contractions on both legs separately. Eccentric exercise impaired maximal force and increased ratings of muscle soreness (p<0.05). Post supplementation, blood %n-3PUFA/total PUFA was greater in FO (36 +/- 6) vs. PRO (24 +/- 3, p<0.05) and CHO (23 +/- 2, p<0.05). Maximum force loss during recovery tended (p = 0.10) to be less in FO (-19 +/- 22%) vs. CHO (-30 +/- 10%). Muscle soreness (dominant leg), expressed as AUC during 72 h exercise recovery, tended to be less in FO (791 +/- 549 mm x 72 h) vs. PRO (1403 +/- 779 mm x 72) andCHO (1298 +/- 621 m x 72 h p=0.10). The blood concentration of c-reactive protein tended (p=0.09) to be lower in FO (AUC: 42 +/- 11 mg/L x 72 h) vs. CHO (AUC: 83 +/- 42 mg/L x 72 h, p<0.05). FO elicited a possibly (82-85%) beneficial effect on counter movement jump performance vs. PRO and CHO. In summary, a juice-based multi-ingredient beverage, containing n-3PUFA, whey protein and vitamin D, appears to mediate a reduced feeling of muscle soreness after eccentric exercise and translates into improved muscle function and soccer-specific performance during acute recovery. Hence, the benefit of whey protein ingestion to exercise recovery in competitive soccer players is enhanced by adding n-3PUFA and vitamin D.